Clinical and Biochemical Features of Kids with COVID-19 Febrile Seizures during the Omicron Wave - Shi, Yu; Miao, Shijian; Shen, Guomei; Fu, Jin; Gao, Xuan; Du, Xiaonan; Huang, Guoying; Zhou, Shuizhen; Zhai, Xiaowen (Journal of Pediatric Infectious Diseases, 2024)
Objective Mild symptoms are the norm for children with coronavirus disease-2019 (COVID-19), but data on the Omicron form are few. One of the most frequent neurological symptoms of COVID-19 in children is febrile seizure (FS).Methods Patients with FS who visited the pediatric fever clinic between December 6 and December 31, 2022, when the Omicron version of SARS-CoV-2 was the predominant strain, were included in this retrospective, single-center analysis.Results Children who tested positive for COVID-19 had a 5.58% incidence of FSs. Compared to patients without COVID-19, a greater percentage of COVID-19 patients (29.5 vs. 7.5%, p < 0.01) experienced complex FSs. In the COVID-19-positive group, four cases were critically unwell and were admitted to the Intensive Care Unit (1.4 vs. 0%, p < 0.01), and the admission proportion was greater (18.9 vs. 1.9%, p < 0.01). The proportion of lactic acid and IL-6 increase was larger in the COVID-19-positive group (33.5 vs. 21.5%, 22.1 vs. 17.8%, p = 0.022, p = 0.006, respectively).Conclusion Infections with COVID-19 in children have been linked to FSs in the Omicron era. To fully understand the neuropathogenesis of seizures in children with COVID-19, more research is required.
Keywords: febrile seizures; COVID-19; Omicron; pandemic; convulsions